Protective effect of Clostridium tyrobutyricum in acute dextran sodium sulphate-induced colitis: differential regulation of tumour necrosis factor-α and interleukin-18 in BALB/c and severe combined immunodeficiency mice - Hudcovic, T; Kolinska, J; Klepetar, J; Stepankova, R; Rezanka, T; Srutkova, D; Schwarzer, M; Erban, V; Du, Z; Wells, J M; Hrncir, T; Tlaskalova-Hogenova, H; et al. (Clinical and experimental immunology, 2012)
One of the promising approaches in the therapy of ulcerative colitis is administration of butyrate, an energy source for colonocytes, into the lumen of the colon. This study investigates the effect of butyrate producing bacterium Clostridium tyrobutyricum on dextran sodium sulphate (DSS)-induced colitis in mice. Immunocompetent BALB/c and immunodeficient severe combined immunodeficiency (SCID) mice reared in specific-pathogen-free (SPF) conditions were treated intrarectally with C. tyrobutyricum 1 week prior to the induction of DSS colitis and during oral DSS treatment. Administration of DSS without C. tyrobutyricum treatment led to an appearance of clinical symptoms - bleeding, rectal prolapses and colitis-induced increase in the antigen CD11b, a marker of infiltrating inflammatory cells in the lamina propria. The severity of colitis was similar in BALB/c and SCID mice as judged by the histological damage score and colon shortening after 7 days of DSS treatment. Both strains of mice also showed a similar reduction in tight junction (TJ) protein zonula occludens (ZO)-1 expression and of MUC-2 mucin depression. Highly elevated levels of cytokine tumour necrosis factor (TNF)-α in the colon of SCID mice and of interleukin (IL)-18 in BALB/c mice were observed. Intrarectal administration of C. tyrobutyricum prevented appearance of clinical symptoms of DSS-colitis, restored normal MUC-2 production, unaltered expression of TJ protein ZO-1 and decreased levels of TNF-α and IL-18 in the descending colon of SCID and BALB/c mice, respectively. Some of these features can be ascribed to the increased production of butyrate in the lumen of the colon and its role in protection of barrier functions and regulation of IL-18 expression.
Keywords: interleukin-18; Animals; Probiotics; kolon; mastné kyseliny; Acute Disease; fosfoproteiny; butyráty; myši SCID; Fatty Acids; Tumor Necrosis Factor-alpha; Administration, Rectal; CD11b Antigen; Colon; mucin 2; Phosphoproteins; síran dextranu; Butyrates; Mice; bakteriální translokace; Dextran Sulfate; membránové proteiny; Mucins; Mice, Inbred BALB C; Mice, SCID; myši; Colitis, Ulcerative; aplikace rektální; TNF-alfa; muciny; Clostridium tyrobutyricum; myši inbrední BALB C; probiotika; Severe Combined Immunodeficiency; ulcerózní kolitida; těžká kombinovaná imunodeficience; Specific Pathogen-Free Organisms; protein zonula occludens 1; Membrane Proteins; imunokompetence; akutní nemoc; Mucin-2; zvířata; Bacterial Translocation; Interleukin-18; Immunocompetence; antigeny CD11b; Zonula Occludens-1 Protein; organismy bez specifických patogenů